Beberapa Potret Pendidikan Keluarga Islam dalam Al-Quran - Noorthaibah Noorthaibah (UIN Sultan Aji Muhammad Idris Samarinda, 2010)
The family is the smallest group within a society. Because society is the set of a few families so good or poor a society is very dependent on good or poor families. Islam gives great attention in coaching and family education. In Islam, monotheism became the foundation and footing family education. Al-Quran as the primary source of Islamic educational value gives instructions and guidance on how the family should be nurtured and educated. In the Al-Quran there are several portraits of family education which fostered over the values of family unity to achieve a good and prosperous. Portrait of family education is described in the Al-Quran on the family of 'Imran, Family of Lukman, the family of the Prophet Ibrahim and Prophet Shu'aib as. In a series of stories the Al-Qur'an it is implied that the family education should be fostered on the value of unity, firmness and patience.